ANALYSIS OF REGIONAL COMPETITIVENESS IN PROMOTING FOREIGN INVESTMENT (PMA) IN RIAU PROVINCE - Muhammad Syahrial '; Wahyu Hamidi ' (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
This research was conducted in the province of Riau , in the city of Pekanbaru is the capital of Riau province that is currently increasing its economic development. This study aim to analyze regional competitiveness in encouraging foreign direct investment (FDI) in Riau Province. Having regard to the economic sectors and infrastructure base. This study uses time series data between the years 2006-2011, using the Location Question (LQ) with qualitative descriptive analysis to analyze the sectors that affect foreign investment. The results of this study indicate that during the period 2006-2011 leading sectors Riau province is owned by four sectors , namely agriculture , construction sector , the sector of Commerce , hotels and restaurants , and the services sector . This is because the value of LQ in each of these sectors is above 1 . Not all sectors of the base that is in the province of Riau, which could encourage foreign investment as the four sectors, the sector was able to absorb the non base of foreign investors to invest in the province of Riau as happened in the manufacturing sector , this is evidenced by the many processing industries are becoming targets of foreign investors to invest . Availability Infrastructure does not fully affect foreign investment in the province of Riau , Based on the calculations, Nilar R2 is 0.3943 figure is explained that the rise and fall of FDI during 2006-2011 amounted to 39.43 % influenced by the ups and downs of a long road infrastructure , the capacity of the electrical energy , the number of bridges and water , as well as wage rates , and the rest is influenced by other factors. From the analysis conducted , it can be concluded that the investments made by foreign investors in Riau province from year to year during 2006-2011 has always fluctuated . The high competitiveness of the region greatly affect the interests of investors in investing , investments made by foreigners is still at the base sectors , investment in infrastructure is needed for the attraction of investment is higher with better infrastructure conditions .Kata Kunci : Competitiveness, Foreign Investment, Infrastructure